The Myth of Comoving Commodity Prices - McDermott, C. (IMF Working Papers; Working Paper, 1999)
There is a common perception that the prices of unrelated commodities move together. This paper re-examines this notion, using a measure of comovement of economic time series called concordance. Concordance measures the proportion of time that the prices of two commodities are concurrently in the same boom period or same slump period. Using data on the prices of several unrelated commodities, the paper finds no evidence of comovement in commodity prices. The results carry an important policy implication, as the study provides no support for earlier claims of irrational trading behavior by participants in world commodity markets.